Pengembangan Model Belajar Inquiry Sebagai Upaya Peningkatan Produktivita Di Kelas - Luluk Khairunnisa; Putri Annisa (Lembaga Pengembangan Kinerja Dosen, 2023)
The research purposed to increase students motivation and used variation of teaching methods teachers in the delivery materials of students. It causes problems faced today, teachers spend too much time in front of classroom without give a chance students to explore new things besides in the class. Another programs is the low critical thinking ability of students which can be seen from the questions and students answer during the learning process. This is accordance with the results shown by Program for International Study Assesment (PISA) in 2015, Indonesia position as one the lowest ranked in quality, Education is ranked 62nd out of 70. Inquiry learning model is one of the way solves this problem. From the facts obtained, the writters tried to provide solutions of these problem is the right to do the development of teaching inquiry learning model. The design of this study using basic research. By using the inquiry learning model, the things obtained is inquiry training requires insvetigative activities, either observation or experiment, which or part of scientific performance. Inquiry involves process skill based on a scientific atittude so that activity can help students to gain a deeper understanding of the environment.